Precios de productos almacenables: implicaciones del modelo de inventarios - Bobenrieth, Eugenio (Estudios de Economía, 2016)
Stock variations are recognized, by market participants and by the literature, as relevant in the determination of prices of storable assets. This paper presents results in the literature of rational expectations dynamic models based on stock variations, to explain price variations. The non-negativity restrictions in aggregate storage induce endogenous non-linearity in the market demand for the asset. The model generates empirical regularities observed in price series: occasional sharp price increases, periods of stability, positive serial correlation, and conditional (and limit) asymmetry in the price distribution.